O PAPEL MODERADOR DE POTÊNCIA DE EQUIPES SOBRE AS RELAÇÕES ENTRE PERCEPÇÃO DE SUPORTE SOCIAL E BEM-ESTAR SUBJETIVO - Oliveira, Maisa Sangy Guedes de (2014)
This research had the purpose to investigate the moderating role of team potency on the relationship between social support perception and subjective well-being among scout teenagers through longitudinal delineation. The team potency are related to the members belief in effectiveness of the team, while the social support is the person´s belief in getting support from his social network. As for the subjective welfare it shows how a person is satisfied with his own life.This research had the participation of 249 teenagers from 53 teams. Each team was made up of three to seven members and their average age was 13,85 years old (SD= 1,86), and 57,4 per cent was male. The research happened among scout troops whose centers were located in Belo Horizonte and Contagem, Minas Gerais. The method used was a questionnaire that each scout should fill in. It had three scales which measured the three variables of this study. The results demonstrated that the social support perception and the team potency influenced positively and significantly the teenager subjective welfare, however, team potency was not able to moderate the relationship between social support perception and subjective welfare. The teenagers kept levels of social support perception and belief in team potency in similar plateaus. Therefore, they enjoyed well-being and mental health, condition that has remained over time. Such evidence assure the role promoter of subjective well-being as well as social support and team potency in individuals mental health.